Das Lächeln des Prometheus - Mythenspiele. - Binder, Steffen; Boström, Jörg; Brinkmann, Rainer Jonn; Diller, Thomas; Wöstheinrich, Bernhard (Bielefeld : Kerber Verlag, 1995)
Albrecht, Udo ; Binder, Steffen ; Bork, Tammo ; Boström, Jörg ; Braun, Jan ; Brinkmann, Rainer Jonn ; Diller, Thomas ; Gayk, Christopher ; Geyer, Andrea ; Hagenbäumer, Detlef ; Haselbach, Marc ; Heerdt, Mechthild ; Hermjohannknecht-Schulz, Martina ; Hoffmann, Peter ; Kuhne, Michael ; Leonhard, Alfred ; Möller, Peter ; Schmidt, Jörg ; Schröder, Hans ; Schuck, Nicole ; Skiba, Zuzanna ; Stork, Anne Katrin ; Vlachopoulos, Stella ; Wesemann, Frauke ; Wöstheinrich, Bernhard
CD-rom zie speciale kast
bibliog. p. 71
biog. p. 70
Duits
Das Lächeln des Prometheus - Mythenspiele, Daniel-Pöppelmann-Haus, Herford, 1. Juli bis 27. August 1995
boek